2010
DOI: 10.1007/s11213-010-9186-0
|View full text |Cite
|
Sign up to set email alerts
|

A Systemic Model for Managing and Evaluating Conflicts in Organizational Change

Abstract: Change or innovation diffusion is a key issue for most business organizations but is yet difficult to implement as the change management process is often complex as it relies on an organized methodology to complement an organization's commitment and participation. An ambiguous environment surrounding change mechanism tends to develop unintended attitudes, resulting in resistance and conflict. The study proposes a model for the management of such conflicts among change participants (involved and affected) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
0
16
0
2
Order By: Relevance
“…The effect of interpersonal justice disappeared when we accounted for the role of relational conflict. The threat of interpersonal conflict looms large in change situations (Raza & Standing, ) and is particularly likely when employees cannot draw from relevant relational resources in their relationships with their supervisor, such as when they experience unfair treatment (Hobfoll, ). Our study has shown that reducing this threat is critical to building positive attitudes toward organisational change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of interpersonal justice disappeared when we accounted for the role of relational conflict. The threat of interpersonal conflict looms large in change situations (Raza & Standing, ) and is particularly likely when employees cannot draw from relevant relational resources in their relationships with their supervisor, such as when they experience unfair treatment (Hobfoll, ). Our study has shown that reducing this threat is critical to building positive attitudes toward organisational change.…”
Section: Discussionmentioning
confidence: 99%
“…4 In all, this study highlights the role of hitherto underexplored facets of relationship quality-interpersonal justice, social interaction, and relational conflict-when it comes to employees' ability to cope with the stress and anxiety that accompany organisational change. In the process of change implementation, interpersonal disagreements inevitably arise between change recipients and their supervisors (Raza & Standing, 2011); we pinpoint such relational conflict as a critical conduit through which fair treatments, or the lack thereof, inform commitment to change. Yet the greatest insight of this study may be our identification of the dual role of social interaction.…”
Section: Theoretical Implicationsmentioning
confidence: 94%
See 2 more Smart Citations
“…Often this either does not fully happen or means additional stretch for their managers (Atkinson, 2003). The fourth point refers to the fact that the conflict might be rooted in the change which is inscribed into matrix management (Joyce, 1986;Raza and Standing, 2011). Projects are started and come to a close, responsibilities are often shifted as the initiatives progress.…”
Section: Motivation and Job Satisfactionmentioning
confidence: 99%